КУРАШЧИЛАРНИНГ ТЕХНИК ҲАРАКАТИНИ ТАКОМИЛЛАШТИРИШ - Еримбетов, Б.Қ. (SCIENCE and SOCIETY, 2023)
This article provides information on improving the technique of movements of kurash wrestlers through training and competitive loads.